REDESIGN UI/UX SEKOLAHDESAIN.ID MENGGUNAKAN METODE DESIGN THINKING DI PT SOLUSI DESAIN BANGSA - Enggal Robed Jayusman; Hadi Sucipto; Reza Augusta Jannatul Firdaus; Sri Widoyoningrum (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrack: Digital transformation has revolutionized education, making online learning crucial. Online platforms offer flexibility, but their success hinges on optimal UI/UX. Poor UI/UX design leads to frustration and user abandonment. High-quality UI/UX analysis is increasingly vital for startups, as good design enhances valuation. Sekolahdesain.id, a platform by PT Solusi Desain Bangsa, aims to enhance graphic design skills but faces challenges with inconsistent navigation and visual presentation. This research applies a Design Thinking approach to create innovative and measurable solutions, emphasizing user needs. The goal is to create a user-friendly and effective learning platform, improving both aesthetics and functionality. Research results show a Maze Usability Score of 57 (moderate) for the account registration landing page (5 users), and 71 (moderate) for the redesigned quiz. The average SUS score of 78.85 (Grade B,